Peter's Motive for Quoting Proverbs 11:31 as an Encouragement to Be Righteous - Pattinaja, Aska Aprilano; Kiamani, Andris; Sualang, Farel Yosua (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
Proverbs 11:31 is an Old Testament passage of wisdom quoted by Peter in 1 Peter 4:18. Based on the literature search, there are two interpretations related to this intertextual use of Scripture, namely talking about retribution or divine justice and moral responsibility. But it was found that previous studies did not mention anything about Peter's motive in quoting this wisdom literature narrative. Therefore, this study aims to specifically examine Peter's motives in quoting this Old Testament passage. There are strong implications of the Wisdom literature exhortations quoted by Peter as an encouragement to the early church to choose to live as righteous people.   Therefore, this research used qualitative methods with a sub-interpretive design, specifically wisdom literature hermeneutics and literature study. This article finds that Peter's motivation for encouraging the believers was that they should never envy the oppressors and persecutors because those who reject the gospel will suffer more than anything Christians have to face in this life. God is just, and His judgment will apply to everyone, including the wicked. Peter's motive for quoting the Old Testament also serves as a theological and practical guide for believers, enabling them to live in a way that reflects their faith and trust in God's final judgment and deliverance.